Understanding muscle properties in sports performance optimization - Herzog, W. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
Understanding muscle properties in the context of sports movements is crucial for maximizing power output, minimizing the cost of transport, or delaying fatigue. Here, we review the three basic properties of skeletal muscles that affect optimal working performance: the force-length, the force (power)-velocity, and the time-dependent force properties. We demonstrate on two examples (cycling and cross-country skiing) how knowledge of muscle properties can help maximize sport performance.